Genetic analysis of anthracnose resistance in Jalo Pintado 2 dry bean cultivar - Frias, A. A. T. (2014)
Anthracnose, caused by the fungus Colletotrichum lindemuthianum (Sacc. and Magnus) Briosi and Cavara, is one of the most widespread and economically important diseases of common bean (Phaseolus vulgaris L.) worldwide (Pastor-Corrales and Tu, 1989). Search for new sources of resistance have been the objective of many breeding programs, since genetic resistance is the most effective and environmentally friendly management strategy for the control of anthracnose disease in common bean. Therefore, this study aimed to investigate the genetic resistance to anthracnose in the Andean cultivar Jalo Pintado 2.